A comparative study of stylistic kriging and Co - kriging Multivariate on the barley crop in Iraq - محمد, جعفر موسى (Journal of Economics and Administrative Sciences, 2014)
This paper deals  the prediction of the process of  random spatial data of two properties, the first is called  Primary variables  and the second is called secondary  variables ,   the method  that were used in the  prediction process for this type  of data is technique Co-kriging  , the method is usually used when the number of primary variables  meant to predict for one of its elements is measured in a particular location a few (because of the cost or difficulty of obtaining them) compare with secondary variable which is the number of elements  are available and  highly correlated with primary variables, as was the  application of the prediction process in a manner kriging only primary variables  and we compared  prediction  result between C0-kriging and kriging technique  to knowledge  the best method for these cases.